STUDI NUMERIK KARAKTERISTIK ALIRAN SILANG PADA SILINDER BUNDAR TUNGGAL - Fajar, Berkah (Mesin, 2008)
This study deals with numerical investigation of hydrodynamic properties of fluids flow accross a single circular cylinder. The flow is assumed incompressible, laminar with Reynolds number 0,0001, 2, 20, 40, 100, 200, 400, 1000, 4000 and 20000. The work started with generating geometrical mesh, and then continue with the numerical simulation. The simulations were done by varying the pressure with standardm linier or second order interpolation, momentum discretisation (first-order upwind, second-order upwind, Power law), and pressure velocity coupling (SIMPLE, SIMPLEC, and PISO). The simulation results agree with the experimental results done by other. The comparison parameter used were flow pattern, Strouhal number, drag coefficient, and separation position. The simulation results also show that the flow characteristic with Reynolds Number larger than 40 is depend on time (unsteady). This is caused by vortex shedding at the rear of the cylinder. The body force (lift and drag) on the cylinder change periodically and the value agree with the experimental results.